Enhancing Program Quality in a National Sample of After‐school Settings: The Role of Youth–Staff Interactions and Staff/Organizational Functioning. Issue 3 (4th April 2019) - Kuperminc, Gabriel P.; Seitz, Scot; Joseph, Hannah; Khatib, Nadim; Wilson, Christyl; Collins, Krista; Guessous, Omar
Abstract: Using multilevel data from the national evaluation of Boys and Girls Clubs of America (BGCA), this study examined associations among programmatic structures, workplace and workforce characteristics, and relational practices of program staff as they relate to young people's ratings of their experience attending local clubs. The sample included 57, 710 members and 5, 231 staff members at 740 BGCA sites throughout the United States. Staff relational practices—including establishing caring relationships, setting high expectations, positive behavior management, encouraging youth input and agency, and cultural sensitivity—explained associations between staffing and organizational functioning and youths' perceptions of the quality of their clubs. Findings suggest a central role of staff relational practices in establishing conditions that youth experience positively, and that staffing and organizational processes, including community engagement and teamwork and efficiency can be viewed as foundations for establishing a culture of positive adult‐youth interaction, which in turn can contribute to the promotion of positive youth development. Further, identification with the experiences of youth had a direct association with youths' perceptions of club quality. These results underscore the importance of staff workforce development initiatives as key to improving youth experiences in after‐school programs. Highlights: Staff relational practices mediate relations of organization functioning and perceived quality. Staffing and organizational processes underlie a culture of positive adult–youth interaction. Staff identifying with the experiences of youth contributes to youths' perceptions of club quality. Results underscore the importance of workforce development in after‐school programs.